MAGNETIC PROPERTIES OF RARE EARTH THIOPHOSPHATES REPS4 - Zhongle H.; Victoria C.; Philippe M. (My University, 1999)
The magnetic susceptibilities of REPS4(RE = La-Yb) compounds series were measured in the temperature range of 2-300 K. The variations of the susceptibility and the inverse susceptibility along with the temperature were studied for each case. The Curie-Weiss constants(C and ⊖ and the effect moment μeff for each paramagnetic RE3+ were obtained by simulating the susceptibility data measured in the temperature range of 50-300 K.